(untitled) (Asian Education Studies, 2016)
This article discusses the impact that both input and output hypotheses have on second language learning. For decades, there have been opposing ideas in this regard. Several studies were consulted to have a clearer view of which approach is more recommendable for people involved in language teaching. For several years teachers of second language strongly believed that learning a new language depended on the exposition of learners to the target language. For effective learning, the exposition should be higher than the students’ level but comprehensible enough for them to understand. However, this hypothesis was rejected when a new study revealed that the exposition was not enough. Students need to use the language they have learnt. These new ideas emerged from the output hypothesis that had a significant impact on the field of language teaching. The article concludes that both approaches can be used complementarily although more study is still needed.